War makes me sad = (Malungkot ako kapag may digmaan) - Ordinario, Mary Ann; Rolando Nolasto C. Royong II (Plaridel St., Kidapawan City, Philippines ABC Educational Development Center, 2018)
"The war in Mindanao between Muslims and Christians is very real and this is how an innocent child experiences it. Feel their fear, tragedy, suffering, and their longing for peace."--Pumplepie Books & Happiness.
"April 2018"--Title page verso.
Texts in English with Filipino translation.
"Winner, Best Short Story for Children 2003-The Catholic Mass Media Awards."--Cover.
"Second prize winner [of the] Samsung KidsTime Author's Award, 2016 AFCC Singapore"--Cover.
Keywords: Children and war -- Philippines -- Mindanao -- Juvenile fiction; Islam -- Relations -- Christianity -- Juvenile fiction; Children's stories, Philippine (English); Children's stories, Filipino